Modernisasi Pendidikan Islam di Indonesia (Komparasi Pengalaman Organisasi Muhammadiyah dan Nahdlatul Ulama) - Daulay, Saripuddin; Dalimunthe, Rasyid Anwar (Fitrah: Journal of Islamic Education, 2021)
This study aims to analyze the modernization of Islamic education in Indonesia from two organizations namely Muhammadiyah and Nahdlatul Ulama. The focus of the study is on aspects of modernization and the contribution of modernization to national education. This type of research is qualitative based on literature study. The results of the study explain that aspects of modernization, such as educational goals, Muhammadiyah directs it towards being firm in holding and practicing Islamic teachings sourced from the Qur'an and Hadith. Meanwhile, Nahdlatul Ulama aims to be moral-spiritual oriented which emphasizes the urgency of balance between religion and science. Aspects of the curriculum, Muhammadiyah and Nahdatul Ulama have something in common, namely incorporating science into their curriculum. There is almost no difference in the method aspect, although NU sometimes still maintains its classical methods such as Wetonan and Sorogan. Both aspects of human resource development demand to have the characteristics of organizational scholarship. Its contribution to the national education system, Muhammadiyah gave birth to schools with Islamic curricula which so far only taught science, the NU version gave birth to modern Islamic boarding schools, even tiered to the level of higher education.